Analysis of the Influence of Tambakrigagadung Landfill Leachate Characteristics on Water Quality and Heavy Metal Contamination of Reservoirs, Tikung District, Lamongan Regency - Prasidya, Denaya Andrya; Hendrawanto , Feri; Wilda Aniriani, Gading; Sulistiono , Eko (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
The Final Disposal Site (TPA) of Tambakrigadung Village, Lamongan Regency, implements a semi-sanitary landfill system in which waste processing still piles up piles of waste with soil for a certain period, causing a foul odor due to the leachate that collects. Leachate that is not managed correctly is feared to flow into reservoirs as irrigation and productive land that is used by local communities for rice fields or ponds around the Tambakrigadung TPA so that it can disrupt workers, reduce the quality and yield of rice fields, and affect the development of pond fish around the Tambakrigadung landfill. This research aims to test the quality of reservoir water, which refers to the leachate water quality standards of PermenLHK RI No. P.59 Tahun 2016. It analyzes the influence of leachate on reservoir water around Tambakrigadung. The method used in this research is grab sampling. Analysis of pH, BOD, COD, and TSS parameters using simple linear regression quantitative analysis. Quantitative parameter analysis shows that TPA Tambakrigadung leachate influences the pH and TSS parameters of reservoir water in Tikung District, Lamongan Regency, which is indicated by a significance value of <0.05. The analysis of heavy metal parameters shows that the leachate does not meet quality standards, with a total N of 187.7 ppm and cadmium of 0.15 ppm. The mercury parameter meets quality standards, namely 0.00065 ppm. Meanwhile, heavy metal parameters in reservoir water have met quality standards based on PP No. 22 of 2021.